Iminodiacetate complex of cobalt(II) – Structure, physicochemical characteristics, biological properties and catalytic activity for 2-chloro-2-propen-1-ol oligomerization. (1st January 2020) - Drzeżdżon, Joanna; Malinowski, Jacek; Sikorski, Artur; Gawdzik, Barbara; Rybiński, Przemysław; Chmurzyński, Lech; Jacewicz, Dagmara
Graphical abstract: The iminodiacetate cobalt(II) complex is a new highly active catalyst for the 2-chloro-2-propen-1-ol oligomerization. The antioxidant activity of [Co(ida)(H2 O)2 ] against superoxide anion radical has been confirmed. It is very interesting to note that the NBT test results have shown that the tested complex is a stronger antioxidant than l -ascorbic acid. Abstract: A coordination complex, [Co(ida)(H2 O)2 ] where ida denotes iminodiacetate, as a potential highly active catalyst was designed and obtained. To obtain a full structural characteristic, i.e. to determine the crystallographic details and the spatial structure of the crystals of the studied complex, X-ray analysis was carried out. [Co(ida)(H2 O)2 ] was investigated also by elementary analysis, IR spectrophotometry and MALDI-TOF-MS to get a full physicochemical characteristics. The stoichiometry of [Co(ida)(H2 O)2 ] in aqueous solutions was determined using the conductometric titrations. Consequently, the potentiometric titrations were performed to determine the thermodynamic stability of the title compound in aqueous solutions. Moreover, the antioxidant activity of [Co(ida)(H2 O)2 ] against superoxide anion radical has been examined by NBT test. The catalytic properties of the cobalt(II) complex, [Co(ida)(H2 O)2 ], were examined. It turned out that complex studied is a highly active catalyst for the 2-chloro-2-propen-1-ol oligomerization. It catalyzes the reaction of oligomerization in mild conditions: under normal pressure and at room temperature. The oligomerization reaction products were fully characterized by the following spectroscopic methods: IR, NMR, MALDI-TOF-MS. Furthermore, to investigate the thermal behavior of the obtained oligomer, the product of the oligomerization obtained using [Co(ida)(H2 O)2 ] as the catalyst was studied with the use of thermal analysis methods, i.e. DSC and TG. The catalytic activity of the title complex has also been calculated.